Odpowiedź :
1przyklad.
y=ax+b
0=-3a+b
6=a+b/*3
0=-3a+b
18=3a+3b
18=4b/:18
b=4,5
0=-3a+b
6=a+b/*(-1)
0=-3a+b
-6=(-a)+(-b)
0=-3a+b
-6=-4a/:(-4)
a=1,5
y=1,5x+4,5
inne przyklady zrob sam an podstawie:)
y=ax+b
0=-3a+b
6=a+b/*3
0=-3a+b
18=3a+3b
18=4b/:18
b=4,5
0=-3a+b
6=a+b/*(-1)
0=-3a+b
-6=(-a)+(-b)
0=-3a+b
-6=-4a/:(-4)
a=1,5
y=1,5x+4,5
inne przyklady zrob sam an podstawie:)
1. A=(-3,0) b=(0,6)
∫0=3a+b
∫6=a+b /×(-1) To jest Funkcja
∫0=3a+b
∫-6=-a-b +
-6=2a
-3=a
-6=-3+b
b=-6+3
b=-3 , y=-3x-3
2.
A=(-2,3) B=(1,-3)
∫3=-2a+b
∫-3=a+b /×(-1)
∫3=-2a+b
∫3=-a-b +
6=-3a /:(-3)
-2=a
3=-(-2)-b
3=2-b
b=3-2
b=1
y=-2x+1
3.
A=(0.4) B=(-1,-3)
∫4=a+b
∫-3=-1a+b /×(-1)
∫4=a+b
∫3=a-b +
2a=7 /:2
a=3.5
3=3.5-b
b=3-3.5
b=-0,5
y=3,5x-0,5
4,
A=(1,5) B=(-2,-1)
∫5=a+b /×2
∫-1=-2a+b
∫10=2a+2b
∫-1=-2a+b +
9=3b /:3
b=3
5=a+3
a=5-3
a=2
y=2x+3
5.
A=(2,3) B=(3,2)
∫3=2a+b
∫2=3a+b /×(-1)
∫3=2a+b
∫-2=-3a-b +
1=-a /×(-1)
-1=a
3=2×-1+b
3=-2+b
b=3+2
b=5
y=-1x+5
6.A=(-2,5) B=(-1,1)
∫5=-2a+b
∫1=-1a+b /x(-1)
∫5=-2a+5
∫-1=a-b +
4=-a /x(-1)
-4=a
-1=-4-b
-b=-1+4
b=-3
y=-4x-3
7,A=(1,7) B=(-1,1)
7=a+b
1=-1a+b /x(-1)
7=a+b
-1=a-b +
6=2a /:2
3=a
7=3+b
b=7-3
b=4
y=3x+4
8.A=(1,2) B=(2,0)
2=a+b
0=2a+b /x(-1)
2=a+b
0=-2a-b +
a=-2
2=-2+b
b=2+2
b=4
y=-2x+4
9.A=(3,0) B=(0,4)
0=3a+b
4=a+b /x(-1)
0=3a+b
-4=-a-b +
-4=2a
a=-2
-4=-(-2)-b
-4=2-b
b=-4-2
b=-6
y=-2x-6
10.A=(4,0) B=(3,2)
0=4a+b
2=3a+b /x(-1)
0=4a+b
-2=-3a-b +
-2=-a
a=2
2=3×2+b
2=6+b
b=2-6
b=-4
y=2x-4
Sorki że długo.. ale strasznie duzo Licznia.. i pisania..:p
∫0=3a+b
∫6=a+b /×(-1) To jest Funkcja
∫0=3a+b
∫-6=-a-b +
-6=2a
-3=a
-6=-3+b
b=-6+3
b=-3 , y=-3x-3
2.
A=(-2,3) B=(1,-3)
∫3=-2a+b
∫-3=a+b /×(-1)
∫3=-2a+b
∫3=-a-b +
6=-3a /:(-3)
-2=a
3=-(-2)-b
3=2-b
b=3-2
b=1
y=-2x+1
3.
A=(0.4) B=(-1,-3)
∫4=a+b
∫-3=-1a+b /×(-1)
∫4=a+b
∫3=a-b +
2a=7 /:2
a=3.5
3=3.5-b
b=3-3.5
b=-0,5
y=3,5x-0,5
4,
A=(1,5) B=(-2,-1)
∫5=a+b /×2
∫-1=-2a+b
∫10=2a+2b
∫-1=-2a+b +
9=3b /:3
b=3
5=a+3
a=5-3
a=2
y=2x+3
5.
A=(2,3) B=(3,2)
∫3=2a+b
∫2=3a+b /×(-1)
∫3=2a+b
∫-2=-3a-b +
1=-a /×(-1)
-1=a
3=2×-1+b
3=-2+b
b=3+2
b=5
y=-1x+5
6.A=(-2,5) B=(-1,1)
∫5=-2a+b
∫1=-1a+b /x(-1)
∫5=-2a+5
∫-1=a-b +
4=-a /x(-1)
-4=a
-1=-4-b
-b=-1+4
b=-3
y=-4x-3
7,A=(1,7) B=(-1,1)
7=a+b
1=-1a+b /x(-1)
7=a+b
-1=a-b +
6=2a /:2
3=a
7=3+b
b=7-3
b=4
y=3x+4
8.A=(1,2) B=(2,0)
2=a+b
0=2a+b /x(-1)
2=a+b
0=-2a-b +
a=-2
2=-2+b
b=2+2
b=4
y=-2x+4
9.A=(3,0) B=(0,4)
0=3a+b
4=a+b /x(-1)
0=3a+b
-4=-a-b +
-4=2a
a=-2
-4=-(-2)-b
-4=2-b
b=-4-2
b=-6
y=-2x-6
10.A=(4,0) B=(3,2)
0=4a+b
2=3a+b /x(-1)
0=4a+b
-2=-3a-b +
-2=-a
a=2
2=3×2+b
2=6+b
b=2-6
b=-4
y=2x-4
Sorki że długo.. ale strasznie duzo Licznia.. i pisania..:p